Pelajar Pancasila character development through digital literature in high school - Imas Komala; Ramadiani Ramadiani; Zeni Haryanto (Curricula: Journal of Curriculum Development, 2025)
Digital literature, broadly defined as any text consumed on a screen, creates a reading environment that pulses with interactivity. This research presents a systematic review examining the contribution of digital reading materials to the formation of Pancasila character among high school students in Indonesia. The purpose of this study is to investigate whether digital literature can genuinely help high school students grow into more Pancasila-minded citizens. The methodology employed is a qualitative literature review, analyzing empirical, methodologically sound, pertinent, and recent articles published between 2021 and early 2025. Google Scholar served as the primary search hub, utilizing keyword combinations such as "Pancasila student character" and "digital literature". Findings indicate a robust correlation between digital media and the multifaceted growth of the Profil Pelajar Pancasila. Various modalities, including web comics, e-books, and project-centered digital modules, were found to have significantly raised students' understanding, involvement, and real-world application of Pancasila principles. This literature suggests that when Teachers harness students' native devices and habits, they help a tech-savvy generation anchor its civic identity within Indonesia's enduring ethical framework.   Abstrak Literatur digital, secara umum didefinisikan sebagai teks apa pun yang dikonsumsi di layar, menciptakan lingkungan membaca yang penuh dengan interaktivitas. Penelitian ini menyajikan tinjauan sistematis yang mengkaji kontribusi bahan bacaan digital terhadap pembentukan karakter Pancasila pada siswa sekolah menengah atas di Indonesia. Penelitian ini dilatarbelakangi oleh kesenjangan dalam literatur mengenai pengaruh langsung literatur digital terhadap ciri-ciri karakter Pancasila siswa dan tantangan dalam mengintegrasikan nilai-nilai Pancasila ke dalam pengajaran harian. Metode yang digunakan adalah tinjauan literatur kualitatif, menganalisis artikel-artikel empiris, metodologis, relevan, dan terkini yang diterbitkan antara tahun 2021 dan awal 2025. Sumber utama pencarian adalah Google Scholar, menggunakan kombinasi kata kunci seperti "Pancasila student character" dan "digital literature". Temuan menunjukkan korelasi yang kuat antara media digital dan pertumbuhan karakter Profil Pelajar Pancasila. Berbagai modalitas seperti komik web, e-book, dan modul digital berbasis proyek secara signifikan meningkatkan pemahaman, keterlibatan, dan penerapan prinsip-prinsip Pancasila siswa. Literatur ini mengindikasikan bahwa memanfaatkan perangkat dan kebiasaan digital siswa dapat membantu mengukuhkan identitas kewarganegaraan mereka dalam kerangka etika Indonesia yang abadi. Kata Kunci: karakter pancasila; kurikulum merdeka; literasi digital; literatur digital